2010
DOI: 10.1302/0301-620x.92b8.23980
|View full text |Cite
|
Sign up to set email alerts
|

The effect of anteroposterior laxity on the range of movement and knee function following a cruciate-retaining total knee replacement

Abstract: The amount of anteroposterior laxity required for a good range of movement and knee function in a cruciate-retaining total knee replacement (TKR) continues to be debated. We undertook a retrospective study to evaluate the effects of anteroposterior laxity on the range of movement and knee function in 55 patients following the e-motion cruciate-retaining TKR with a minimum follow-up of two years. The knees were divided into stable (anteroposterior translation, < or = 10 mm, 38 patients) and unstable (anteropost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
33
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 24 publications
(53 reference statements)
2
33
1
Order By: Relevance
“…A single‐radius design oriented along the trans‐epicondylar axis may reproduce the natural knee kinematics19 and maintain isometry of the MCL. Clinical studies8, 20 found that functional scores were reduced only when AP laxity exceeded 10 mm, which is greater than in this experiment, and is related to ligament laxity rather than a relatively small change in implant geometry, between single and multi‐radius femoral components. More knowledge of TKA function could be gained by further experiments, in which component positions, ligament tensions and loading conditions are varied 12, 13.…”
Section: Discussioncontrasting
confidence: 45%
See 2 more Smart Citations
“…A single‐radius design oriented along the trans‐epicondylar axis may reproduce the natural knee kinematics19 and maintain isometry of the MCL. Clinical studies8, 20 found that functional scores were reduced only when AP laxity exceeded 10 mm, which is greater than in this experiment, and is related to ligament laxity rather than a relatively small change in implant geometry, between single and multi‐radius femoral components. More knowledge of TKA function could be gained by further experiments, in which component positions, ligament tensions and loading conditions are varied 12, 13.…”
Section: Discussioncontrasting
confidence: 45%
“…A geometrical analysis (that remains unconfirmed by experimental measurement) suggested that the multi‐radius geometry may tend to tense the sMCL in mid‐flexion more than the single‐radius design. Taking this with clinical evidence7, 8, 20 suggests that mid‐range instability relates to ligament laxity, which may not be recognized during surgery.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Furthermore, soft tissue laxity may negatively infl uence outcome in patients receiving a minimally constrained knee design, such as cruciate retaining knees. 9,10 Patients with fi bromyalgia may also develop end-stage knee arthritis and eventually require total knee arthroplasty (TKA). Currently, no data on the results of TKA in patients with fi bromyalgia have been published.…”
mentioning
confidence: 99%
“…[7][8][9] However, Seon et al, 10 in their assessment of 42 TKRs, have suggested that a moderate amount (5 mm to 10 mm) of sagittal movement may provide ideal function and ROM, compared, for instance, with a TKR that is too tight (< 5 mm) or lax (> 10 mm) when assessed for AP translation. 9,11 The objective of our study was to correlate post-operative AP movement in patients with a CR TKR with ROM and function two years post-operatively.…”
mentioning
confidence: 99%